"On the move, or staying put?" An analysis of intrametropolitan residential mobility and ageing in place. Issue 3 (25th August 2017) - Atkins, Mariana T.
Abstract: Population ageing and urbanisation are worldwide phenomena that are transforming societies and having profound economic and social effects on cities and countries throughout the world. Ageing is not taking place evenly, and in many developed cities, ageing growth rates are greater in peripheral areas than in the centre. This paper determines how intrametropolitan residential mobility and ageing‐in‐place patterns vary across age categories and geographical scales, explored through a case study of metropolitan Perth, a rapidly growing, low‐density, sprawling city. Using a life course perspective, this study examines Australian residential mobility census data between 2006 and 2011 and disaggregates this into 4 age categories: preretirement (ages 55–64), seniors in active retirement (ages 65–74), mature‐aged seniors (ages 75–84), and older aged seniors (over 85 years). This study adds to the internal migration literature by offering new insights into the age‐specific mobility patterns of older populations within metropolitan areas. The results reveal that the overriding dynamic is one of stability across the metropolitan area with the dominant trend being "ageing in place." It was found that the likelihood of residential mobility varies by age, and a 2‐peak mobility pattern was identified, with the preretirement and the older aged seniors exhibiting the most mobility. Additionally, although the majority of moves were short distance, younger ages moved farther than did the older aged categories. The study makes empirical and conceptual contributions to our understanding of ageing residential mobility trends within metropolitan areas.